1958
DOI: 10.1017/s0022149x00019374
|View full text |Cite
|
Sign up to set email alerts
|

On Euparadistomum heischi n.sp. from the Liver of a Domestic Gat on Pate Island, Kenya, and a New Sub-family Euparadistominae (Dicrocoeliidaè)

Abstract: Euparadistomum heischi n.sp., the sixth species in the genus, was recovered from a domestic cat on Pate Island, Kenya. In the Dicrocoeliidae, a new subfamily Euparadistominae is proposed for two genera, Euparadistomum Tubangui, 1931 and Stromitrema Skrjabin and Evranova, 1944.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1962
1962
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Measurements of the worms are given in Table 1. By referring to the key to species in the genus Euparadistomum given by Talbot (1970) and by consulting some of the original papers (Tubangui, 1931;Buckley and Yeh, 1958;Singh, 1958) the present material appears to have the characters common to E. buckleyi Singh and E. pearsoni Talbot which differentiate them from other species in the genus (ventral sucker larger than oral sucker; distended intestinal caeca; smooth body surface; small size of testes). However when considering the characters used to separate the two above mentioned species it is found that the present material has intermediate characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements of the worms are given in Table 1. By referring to the key to species in the genus Euparadistomum given by Talbot (1970) and by consulting some of the original papers (Tubangui, 1931;Buckley and Yeh, 1958;Singh, 1958) the present material appears to have the characters common to E. buckleyi Singh and E. pearsoni Talbot which differentiate them from other species in the genus (ventral sucker larger than oral sucker; distended intestinal caeca; smooth body surface; small size of testes). However when considering the characters used to separate the two above mentioned species it is found that the present material has intermediate characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Cats fed incidentally on reptiles and terrestrial arthropods are often infected with Euparadistomum species. In this scope, Buckley and Sheng-Liang (1958) recorded E. heiwschi from the liver of a domestic cat in Pate Island, Kenya, and Rajavelu and Raja (1988) elucidated E. pearsoni in Papua, New Guinea, E. buckleyi from cats in Madras, India. The last literature reported E. buckleyi for the first record from a cat in India.…”
Section: Description and Biology Of The Flukementioning
confidence: 95%
“…Several decades ago, a domestic cat is considered a new host for Euparadistomum spp. (Buckley and Sheng-Liang 1958). Later, Euparadistomum sp.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of the literature on members of the genus Euparadistomum has been given by Buckley and Yeh (1958) who elucidated the previous confusion and proposed a list of six valid species including E. heischi recorded from the gall bladder of a cat in Kenya by these authors. Since 1958 2 more species have been added to this list, E. buckleyi Singh, 1958 andE.…”
mentioning
confidence: 99%